Economic Traits and Production Performance of Nandanam Quail Reared at Different Cage Stocking Densities - Pandian, C; Sudersan, A; Valvan, S Ezhil; Omprakash, AV (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
This study was carried out to assess the effect of different cage stocking densities on the production performance of Nandanam quail III reared up to 42 days. Three hundred day old Nandanam quail III were randomly assigned to 2.5 x 1.5 ft cages and distributed with 3 treatments (20, 25 and 30 quails per cage or 0.17, 0.14 and 0.11 sq. ft per quail, respectively) and 4 replicates. There were significant differences among treatments for bi-weekly body weight, feed consumption, feed conversion ratio and net profit per bird. There was a reduction (P<0.05) in body weight with the increase in stocking density and the 4th and 6th week body weight were 144.17±3.84, 128.55±3.63 and 108.03±2.69 g; and 216.86±5.95, 207.76±4.01 and 197.27±3.81 g, respectively. The feed consumption per bird (g) up to 42 days were 665.69±0.01, 532.19±0.01 and 443.23±0.01 respectively. Better feed conversion ratio (2.57 and 2.25) and net profit per bird (Rs. 4.48 and 7.15) were observed where the birds reared at the cage stocking density of 0.14 sq.ft and 0.11 sq.ft per bird, respectively. This study concluded that the cage stocking density between 0.11 and 0.14 sq.ft per bird will be more economical for rearing Nandanam quail III in cage system of rearing up to 42 days of age.